PENGEMBANGAN DESA WISATA MELALUI PROGRAM DEWI BAHARI SEBAGAI DESTINASI WISATA BERKELANJUTAN DI DESA PADAK GUAR, KECAMATAN SAMBELIA, NUSA TENGGARA BARAT - Ni Gusti Ayu Samba Desi Putri; I Nyoman Nugraha; Handry Sudiarta Athar (Institut Teknologi dan Bisnis Kristen Bukit Pengharapan, 2026)
This study aims to analyze the role of the Marine Tourism Village Program (Dewi Bahari) in supporting the development of Padak Guar Marine Tourism Village as a sustainable tourism destination. Padak Guar Village possesses various marine tourism attractions, including Kondo Beach, Purwakarya Beach, Pulau Lampu, Gili Kondo, Gili Bidara, and Gili Petagan. This research employed a qualitative case study approach. Data were collected through observation, in-depth interviews, and documentation, involving eight key informants: village government representatives, tourism managers, local business actors, community leaders, youth representatives, and tourists. Data analysis followed the Miles and Huberman model, including data reduction, data display, and conclusion drawing. The findings reveal that the Dewi Bahari Program contributes significantly to tourism development through enhanced tourism attractions, community empowerment, institutional strengthening, destination promotion, and tourism management. However, several challenges remain, including limited human resource capacity, inadequate foreign language skills, insufficient tourism facilities, and varying levels of community participation. Sustainability efforts are implemented through capacity-building programs, service quality improvement, stakeholder collaboration, digital promotion, and coastal environmental conservation. The program has positively contributed to economic, social, and environmental sustainability within Padak Guar Tourism Village.